A Study of Chinese College Students’ English Communicative Competence - Xuefeng, Wang; Xinguang, SHAO (Advances in Social Sciences Research Journal, 2015)
Developing communicative competence plays a very important role in Chinese college students’ English learning. This study investigates how well the students do in using English to communicate with others with the help of questionnaires, which may help them find out some practical strategies to overcome their difficulties in communicating using English. After careful analysis of the means of the subjects’ scores, some causes for the students’ weak communicative competence are found out. They are students’ lack of enthusiasm in using English to communicate, lack of the related cultural background knowledge of English-speaking countries, being afraid of making mistakes, lack of necessary communicating skills, lack of English linguistic knowledge, etc. Some measures should be taken by English teachers to help their students to actively participate in English communication. They should try a lot to encourage their students to make more efforts in order to improve their English communicative competence.